STRUCTURE OF FISH COMMUNITY AND REPRODUCTIYE BIOLOGY OF THREE INDIGENOUS SPECIES OF CYPRINIDS IN KEDUNGOMBO RESERVOIR - Endi Setiadi Kartamihardja (Indonesian Fisheries Research Journal, 1996)
The study investigated the structure of fish community and the reproductive biology of three indigenous species of cyprinids, namely Puntius goninnofas (Bleeker), Puntius bramoid.es (Cuvier & Valenciennes) and Myetacoleucus marginatas (Cuvier & Valenciennes) in the Kedungombo Reservoir, Central Java.